n∑k=1k=n(n+1)2
So I was trying to prove this sum formula without induction. I got some tips from my textbook and got this.
Let S=1+2+⋯+n−1+n be the sum of integers and S=n+(n+1)+⋯+2+1 written backwards. If I add these 2 equations I get 2S=(1+n)+(1+n)⋯(1+n)+(1+n) n times.
This gives me 2S=n(n+1)⇒S=n(n+1)2 as wanted.
However if I changed this proof so that n was strictly odd or strictly even, how might I got about this. I realize even means n must be n/2. But I haven't been able to implement this in the proof correctly.
Edit: error in question fixed, also by n/2 I mean should I implement this idea somewhere in the proof, cause even means divisible by 2.
Answer
Method 1: (requires you to consider whether n is odd or even.)
S=1+2+......+n.
Join up the first to term to the last term and second to second to last and so on.
S=1+2+3+....+(n−2)⏟+(n−1)⏟+n⏟.
=(n+1)+(n+1)+......
If n is even then:
S=1+2+3+..+n2+(n2+1)⏟+..+(n−2)⏟+(n−1)⏟+n⏟
And you have n2 pairs that add up to n+1. So the sum is S=n2(n+1).
If n is odd then:
S=1+2+3+..+n−12+[n+12]+(n+12+1)⏟+..+(n−2)⏟+(n−1)⏟+n⏟
And you have n−12 pairs that also add up to n+1 and one extra number n+12 which didn't fit into any pair. So the sum is n−12(n+1)+n+12=(n−1)n+12+n+12=(n−1+1)n+12n=nn+12.
Method 112 (Same as above but waves hands over doing tso cases).
S=average∗number of terms=average∗n.
Now the average of 1 and n is n+12 and the average of 2 and n−1 is n+12 and so on. So the average of all of them together is n+12. So S=n+12n.
Method 2: (doesn't require considering whether n is odd or even).
S=1+2+3+......+n
S=n+(n−1)+(n−2)+......+1.
2S=S+S=(n+1)+(n+1)+.....+(n+1)=n(n+1)>
S=n(n+1)2.
Note that by adding S to itself this doesn't matter whether n is even or odd.
And lest you are wondering why can we be so sure that n(n+1) must be even (we constructed it so it must be true... but why?) we simply note that one of n or n+1 must be even.
So no problem.
No comments:
Post a Comment